Campur Kode Penggunaan Bahasa dalam Acara Ini Talkshow di Net Tv: Kajian Sosiolinguistik - Rumpiani, Ni Luh Putu; Arnati, Ni Wayan (Humanis, 2019)
The study entitled "Mixed Language Usage Code In This Show Talkshow on Net Tv". There are three problems analyzed in this study, namely the types of code mix, mix language code language and the syntactic categories, and the factors that cause mixed code. The purpose of this study is to describe the types and mixed-code factors contained in the It Talkshow show on Net Tv. To achieve that goal used several methods and techniques. First, the process of collecting data using the method refer, which is assisted with techniques libat libat ably and technique record. Second, the process of data analysis used qualitative descriptive method and the method of agih, which is assisted by techniques of lesap. Third, the presentation of data analysis result is used informal method. The population in this study was 120 videos that aired from January to June 2016 downloaded from the youtube site. Sampling was done by quota sampling with 30 video samples. This research uses the theory developed by Fishman (1971), Jendra (2007), Chaer and Agustin (2010), and Chaer (2014). Based on the analysis that has been done in this show Talkshow on Net Tv, obtained results (1) types of mixed codes found, ie mixed into the code comes from Sundanese, Java, Batak, Betawi, and Bali. The mixed code comes from English and Arabic, and mixed mixed code comes from Sundanese and English; (2) mixed code based on the linguistic level found in the form of clause level, the phrase level is divided into the endocentric phrase and the exocentric phrase, the word level is divided into two, ie the word and the word back, and the syntactic categories found in the form of noun category, verb category, category adjectives, and pronoun categories; and (3) the factors behind the code mix are influenced by participants' speech factor, language factor, and factor of purpose of conversation.